The Effect of PM 10 on Ischemia- Reperfusion Induced Arrhythmias in Rats - Radmanesh,Esmat (2016)
ABSTRACT Epidemiological studies show that particulate matter (PM) is the principal instigator of some adverse clinical symptoms involving cardiovascular diseases. PM exposure can increase experimental infarct size and potentiate myocardial ischemia and arrhythmias in experimental MI models such as ischemia-reperfusion (I/R) injury.The present study was aimed to evaluate the effects of particulate matter (PM10) on ischemia- reperfusion induced arrhythmias with emphasis on the protective role of VA as an antioxidant on them. Male Wistar rats were divided into 8 groups (n=10): Control, VAc, Sham, VA, PM1 (0.5 mg/kg), PM2 (2.5 mg/kg), PM3 group (5 mg/kg), PM3 + VA group. Within 48 hours, PM10 was instilled into trachea in two stages. Then the hearts were isolated, transferred to a Langendorff apparatus, and subjected to global ischemia (30 minutes) followed by reperfusion (60 minutes). The ischemia- reperfusion induced ventricular arrhythmias were assessed according to the Lambeth conventions.In the present study,the number, incidence and duration of arrhythmiasduring30 minutes ischemia were demonstrated to be more than those in the reperfusion stage. PM exposure increased significantly the number, incidence and duration of arrhythmias in the ischemia and reperfusion duration. Vanillic acid reduced significantly the number, incidence and duration of arrhythmias during the ischemia and reperfusion period.In summary, the results of this study demonstrated that the protective and dysrhythmic effects of VA in the PM exposure rats in I/R model are probably related to its antioxidant properties.